Tree species composition and structure of dry forest in Mutis Timau Protected Forest Management Unit of East Nusa Tenggara, Indonesia - AAH AHMAD ALMULQU; NOULKAMOL ARPORNPONG; JARUNTORN BOONYANUPHAP (Biodiversitas Journal of Biological Diversity, 2018)
Almulqu AA, Arpornpong N, Boonyanuphap J. 2018. Tree species composition and structure of dry forest in Mutis Timau Protected Forest Management Unit of East Nusa Tenggara, Indonesia. Biodiversitas 19: 496-503. Plots 10,000 m2 were established in four sites of Mutis Timau Protected Forest Management Unit (Mutis Timau PFMU), in order (Koonkhunthod 2007)to determine tree species density, basal area, importance value index, species richness and to identify the relationship betwen species richness and abundance of trees. A total of 94 species belonging to 72 genera and 45 families were recorded. Species richness and forest structure were different between sites. Moraceae was the dominant tree family at most sites, particulary for Eucalyptus urophylla. The results suggest controlling the number of species, level on species distribution pattern, silvicultural interventions to pioneer species through thinning liberation, seeding and planting (pioneer species) could accelerate the tree regeneration of Mutis Timau PFMU in Kupang District, East Nusa Tenggara Province, Indonesia.